Hepatic Angiomyolipoma: A Case Report and Review of the Literature - Strelčenko, Jekaterina; Kuliavas, Justas; Stratilatovas, Eugenijus; Dulskas, Audrius (Lietuvos chirurgija, 2023)
Background. Hepatic angiomyolipomas are uncommon non-cancerous mesenchymal tumors that belong to the perivascular epithelioid cell tumour group. Smooth muscle cells, fat cells and blood vessels can be observed in these types of neoplasm. Case presentation. We present the case of a 50-year-old patient. The patient was referred to the National Cancer Institute after an abdominal ultrasound, which incidentally revealed a mass in the liver. A whole body computed tomography scan showed a large liver mass, in the VII/VIII/V/VI segments. Trisegmenthomy of the right liver lobe was performed. Pathological examination revealed a rare, but benign tumour – angiomyolipoma. The postoperative course was uneventful and the patient was discharged on postoperative day 9. Two months following the surgery, the patient has no recurrence or late complications. Conclusion. Hepatic angiomyolipoma is a rare, usually benign tumour with malignant potential. It is can be diagnosed by radiological tests, biopsy or after surgery. The most common treatment is surgical resection.